Proyectos para la abolición de la esclavitud en Brasil: las perspectivas de Joaquim Nabuco y Luís Gama - dos Santos, Sales Augusto (2024)
Aiming to contribute to the study of Afro-Brazilian history and culture and, therefore, to stand against the coloniality of power and knowledge, this article aims to compare Joaquim Nabuco’s and Luís Gama’ abolition projects, carrying out a partial survey of their respective characteristics and assumptions. Thus, we verify differences and similarities between their proposals and their political and ideological positions to achieve them. It is argued that the abolition project assumed by Nabuco, understood here as a representative of the ruling elites of that historical context, is diametrically opposed to Luis Gama’s project, a formerly enslaved man who succeeded in becoming an anti-slavery poet and advocate. Both act as organic intellectuals of their classes of origin. The first argued that abolition should be conducted by white free men, but deliberate in Parliament; therefore, without the participation of the enslaved ones and with the ultimate objective of whitening Brazil. The second argued that the conquest of freedom should have effective participation of the enslaved, including the use of violence, such as the murder of the lords by the enslaved.